The mind within the net : models of learning, thinking, and acting - Spitzer, Manfred (Bradford book., 1999)
"How does the brain work? How do billions of neurons bring about ideas, sensations, emotions, and actions? Why do children learn faster than elderly people? What can go wrong in perception, thinking, learning, and acting? Scientists now use computer models to help us understand the most private and human experiences. In The Mind within the Net, Manfred Spitzer shows how these models can fundamentally change how we think about learning, creativity, thinking, and acting, as well as about such matters as schools, retirement homes, politics, and mental disorders."--Jacket